THE APPLICATION OF DISCONTINUATION OF PROSECUTION BASED ON RESTORATIVE JUSTICE IN RELATION TO JOINT CRIMES OF RECEIVING STOLEN GOODS AT THE CILEGON DISTRICT PROSECUTOR’S OFFICE - agus ahmad alisy; Ferry Fathurokhman; Dadang Herli Saputra (Universitas Dharmawangsa Medan, 2026)
Termination of prosecution based on Restorative Justice is carried out by taking into account the interests of victims and other protected legal interests, avoidance of negative stigma, avoidance of retaliation, response and harmony of society, propriety, morality, and public order. There are indications of problems, namely, first, how is the authority of the Republic of Indonesia Prosecutor's Office in terminating prosecution based on restorative justice and second, how is the application of termination of prosecution based on restorative justice to criminal acts of receiving goods carried out jointly at the Cilegon District Prosecutor's Office. This research is a normative juridical research, so the approach used is a case study research approach. The data obtained are analyzed qualitatively. The results of this study indicate that the Prosecutor's Authority in terminating prosecution of criminal cases based on restorative justice is a form of attribution authority, namely authority derived from statutory regulations in this case the Prosecutor's Law and the Termination of Prosecution Regulation because the Public Prosecutor as the case master (dominus litis) has broad authority in resolving criminal cases. The presence of Attorney General Regulation Number 15 of 2020 concerning the termination of prosecution based on Restorative Justice expands the Authority of the Prosecutor in Terminating Cases in the Criminal Procedure Code and expands the Interpretation of the Explanation of Public Interest or in the Interest of Law, of course through a Restorative Justice approach that prioritizes Peace Efforts to compensate for the rights of victims rather than retaliation and the Application of termination of prosecution based on restorative justice for criminal acts of receiving bribes carried out jointly at the Cilegon District Attorney's Office, especially in the case of Hermansyah Maja, et al., who were suspected of violating Article 480 paragraph (1) of the Criminal Code in conjunction with Article 55 Paragraph (1) Ke-1 of the Criminal Code, prosecution should be able to be terminated based on restorative justice because it has fulfilled the requirements as stipulated in Attorney General Regulation Number 15 of 2020 concerning termination of prosecution based on Restorative Justice and there has been peace between the victims and the suspects so that it is in accordance with the purpose of restorative justice, namely to restore the original situation. In addition, the Cilegon District Attorney's Office during the period 2023 to 2025 has terminated prosecution based on restorative justice in 9 (nine) cases so that the authority of the Republic of Indonesia Attorney General's Office in terminating prosecution based on restorative justice is still considered effective and efficient in resolving conflicts in society by involving all related parties (perpetrators, victims, families, and the community) as a real form of humanistic and modern law enforcement, which focuses on restoring the original state, not merely revenge (retributive).